Two components for one resistivity in LaVO3/SrTiO3 heterostructure. (17th February 2015) - Rotella, H; Copie, O; Pautrat, A; Boullay, P; David, A; Pelloquin, D; Labbé, C; Frilay, C; Prellier, W
Abstract: A series of 100 nm LaVO3 thin films have been synthesized on (0 0 1)-oriented SrTiO3 substrates using the pulsed laser deposition technique, and the effects of growth temperature are analyzed. Transport properties reveal a large electronic mobility and a non-linear Hall effect at low temperature. In addition, a cross-over from a semiconducting state at high-temperature to a metallic state at low-temperature is observed, with a clear enhancement of the metallic character as the growth temperature increases. Optical absorption measurements combined with the two-bands analysis of the Hall effect show that the metallicity is induced by the diffusion of oxygen vacancies in the SrTiO3 substrate. These results allow us to understand that the film/substrate heterostructure behaves as an original semiconducting-metallic parallel resistor, and electronic transport properties are consistently explained.